2020
DOI: 10.1136/jitc-2019-000210
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy and limited systemic cytokine exposure with membrane-anchored interleukin-12 T-cell therapy in murine tumor models

Abstract: BackgroundInterleukin-12 (IL-12) is a potent, proinflammatory cytokine that holds promise for cancer immunotherapy, but its clinical use has been limited by its toxicity. To minimize systemic exposure and potential toxicity while maintaining the beneficial effects of IL-12, we developed a novel IL-12-based therapeutic system that combines tumor-specific T-cell-mediated delivery of IL-12 with membrane-restricted IL-12 localization and inducible IL-12 expression.MethodsTherapeutic T cells targeting a tumor antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…In addition to the examples given above, another emerging strategy is to modify the T cell product prior to infusion, thereby “arming” the T cells with the ability to engage endogenous DCs. Recent pre-clinical studies have investigated ACT with genetically modified T cells expressing membrane-anchored IL-12 ( 160 ), which is known to increase co-stimulation by dendritic cells. In addition, T cells engineered to express the DC-recruiting cytokine FLT3L, was recently shown to enhance efficacy and support epitope spreading after ACT therapy ( 161 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the examples given above, another emerging strategy is to modify the T cell product prior to infusion, thereby “arming” the T cells with the ability to engage endogenous DCs. Recent pre-clinical studies have investigated ACT with genetically modified T cells expressing membrane-anchored IL-12 ( 160 ), which is known to increase co-stimulation by dendritic cells. In addition, T cells engineered to express the DC-recruiting cytokine FLT3L, was recently shown to enhance efficacy and support epitope spreading after ACT therapy ( 161 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a CAR T cell secreting the pro-inflammatory cytokine IL-12 demonstrated an improved cytotoxicity and the ability to overcome an immune inhibitory microenvironment in several models, but a clinical trial using IL-12-secreting TILs revealed the high risk of toxicity of this approach if IL-12 secretion is not limited in time and space [ 236 , 237 ]. An attractive strategy to limit cytokine secretion into activated T cells is to use a NFAT-inducible system [ 238 ].…”
Section: Biology Meets Therapy: T-cell Dysfunction In Adoptive Celmentioning
confidence: 99%
“…Additionally, another means of reducing the systemic toxicity of IL-12 could be anchoring iIL-12 to the plasma membrane. In a recent study of tumor mouse models, the toxicity of IL-12 was reduced significantly when applying this approach [84]. IL-12 genetically engineered TILs have been tested in a clinical trial with patients suffering from metastatic melanoma.…”
Section: Incorporating Cytokines To Enhance T Cell Proliferationmentioning
confidence: 99%